The contribution of ergonomics to the effectiveness of the public service: analysis of the implementation of the Electronic Judicial Process (PJe) - Yparraguirre, Ivany Rocha (Brazilian Journal of Operations & Production Management, 2018)
The Brazilian Justice, propelled by the benefits that the technological era can bring to the speed of the jurisdictional provision, proposed the implementation of the Electronic Judicial Process (PJe). In this context of demand for effectiveness, this article aims to identify and evaluate comparatively the ergonomics practices versus the recommendations of the theory on the search of the effectiveness of the Brazilian public service. The analysis focuses on the implantation of the PJe in the Brazilian Courts of Justice and the repercussions on the Quality of Work Life, identifying opportunities for the improvement of the results through the development and application of Ergonomics. The methodological strategy included a review of the literature, field observation, unstructured interviews, document analysis and comparative evaluation of theoretical models and practices in the implantation of the PJe. The results obtained were constituted by a chart illustrating the comparison between practices identified in the implantation of the PC and the possible opportunities of Light Improvements of the literature in Ergonomics. It could be observed that, after almost 10 years since the publication of Law 11,419 / 2006, which defined the implantation of the PJe in the Brazilian Judiciary, there are still few studies that consider and implement care regarding the ergonomic risks and the health and safety of the servers.